Chemistry and oxygen isotopic composition of cluster chondrite clasts and their components in LL3 chondrites. (25th January 2016) - Metzler, Knut; Pack, Andreas
Abstract: Cluster chondrites are characterized by close‐fit textures of deformed and indented chondrules, taken as evidence for hot chondrule accretion (Metzler 2012 ). We investigated seven cluster chondrite clasts from six brecciated LL3 chondrites and measured their bulk oxygen isotopic and chemical composition, including REE, Zr, and Hf. The same parameters were measured in situ on 93 chondrules and 4 interchondrule matrix areas. The CI‐normalized REE patterns of the clasts are flat, showing LL‐chondritic concentrations. The mean chemical compositions of chondrules in clasts and other LL chondrites are indistinguishable and we conclude that cluster chondrite chondrules are representative of the normal LL chondrule population. Type II chondrules are depleted in MgO, Al2 O3 and refractory lithophiles (REE, Zr, Hf) by factors between 0.65 and 0.79 compared to type I chondrules. The chondrule REE patterns are basically flat with slight LREE < HREE fractionations. Many chondrules exhibit negative Eu anomalies while matrix shows a complementary pattern. Chondrules scatter along a correlation line with a slope of 0.63 in the oxygen 3‐isotope diagram, interpreted as the result of O‐isotope exchange between chondrule melts and 18 O‐rich nebular components. In one clast, a distinct anticorrelation between chondrule size and δ 18 O is found, which may indicate a more intense oxygen isotope exchange by smaller chondrules. In some clasts the δ 18 O values of type I chondrules are correlated with concentrations of SiO2 and MnO and anticorrelated with MgO, possibly due to the admixture of a SiO2 ‐ and MnO‐rich component to chondrule melts during oxygen isotope exchange. Two chondrules with negative anomalies in Sm, Eu, and Yb were found and may relate their precursors to refractory material known from group III CAIs. Furthermore, three chondrules with strong LREE > HREE and Zr/Hf fractionations were detected, whose formation history remains to be explained.